2(2x-4)=3(2x-4)
Step 1: Distribute 2 to the numbers in the parentheses on the left side. This would be: (2x - 4) only on the left side
(2 × 2x) + (2 × (-4)) = 3 (2x - 4)
4x + ( -8 ) = 3 (2x - 4)
4x -8 = 3 (2x - 4)
Step 2: Distribute 3 to the numbers in the parentheses on the right side. This would be: (2x - 4) only on the right side
4x -8 = (3 × 2x) + (3 × (-4))
4x -8 = 6x + (-12)
4x -8 = 6x -12
Step 3: Combine like terms
x's go with x's by subtracting 4x to both sides
(4x - 4x) -8 = (6x - 4x) -12
-8 = (6x - 4x) -12
-8 = 2x -12
normal numbers ( -8 and -12) need to be combined. Do this by adding 12 to both sides
(-8 + 12) = 2x + (-12 + 12)
4 = 2x
Step 4: Isolate x by dividing 2 to both sides
2 = x
x = 2
Hope this helped!